Predicting the effect of habitat modification on networks of interacting species - Phillip P. A. Staniczenko (Nature Portfolio, 2017)
In a changing world, the ability to predict the impact of environmental change on ecological communities is essential. Here, the authors show that by separating species abundances from interaction preferences, they can predict the effects of habitat modification on the structure of weighted species interaction networks, even with limited data.